Combined partial denitrification/anammox process for nitrogen removal in wastewater treatment. Issue 1 (February 2023) - Al-Hazmi, Hussein E.; Grubba, Dominika; Majtacz, Joanna; Ziembińska-Buczyńska, Aleksandra; Zhai, Jun; Mąkinia, Jacek
Abstract: Recently, the combined partial denitrification and anammox (PD/anammox) has received special attention as a viable alternative for N removal using organic matter present in municipal wastewater. In comparison with conventional nitrification-denitrification, PD/anammox provides enormous opportunities to achieve sustainable wastewater treatment due to the lack of dissolved oxygen (DO) demand, a smaller amount of organic carbon (C) and less excess sludge production and GHG emissions. The PD/anammox process can be widely carried out in different technical systems, including single- or two-stage systems for side-stream and mainstream wastewater. This review focuses on the latest improvements related to the PD/anammox system and discusses the production/consumption pathways of NO2 - as a critical intermediate. The C/N ratio plays a key role in the PD/anammox process; therefore, the concentration of the dosed organic C is important due to its negative influence on the activity of anammox resulting from the overgrowth of denitrifying bacteria in the systems. Understanding microorganism competition in a one-stage PD/anammox is typically the most important key to optimal efficiency of N removal from mainstream wastewater. Therefore, in this review, a comprehensive description of microbial metabolism i.e., autotrophic anammox, denitrifying heterotrophs/autotrophs, DNRA heterotrophs, and the contiguity competition between them in single-stage PD/anammox systems are inclusively explained. The challenge and limitations are described to recognize inhibition mechanisms and performance inhibitors. The combination of PD/anammox with other processes and the development of a self-supporting bacterial system should be the main lines of future research and efficiency development towards further enhancing total nitrogen removal efficiency (TNRE). Graphical Abstract: ga1 Highlights: Stable NO2 - supply by PD process positively improves efficiencies of NO3 - and NH4 + removal. PD/anammox is suitable in both mainstream and sidestream wastewaters treatment. A deep understanding of microbial competition elaborately helps to apply PD/anammox in WWTP. PD/anammox receives special attention as a promising energy-efficient process for N removal. PD/anammox provides the potential for efficient mitigation of GHG.